السياحة في ضوء السنة وتطبيقاتها على دولة الإمارات العربية المتحدة - محمد، عبدالله إبراهيم عبد الجبار
This study aimed to research tourism in the Islamic perspective through the Prophetic Sunnah and apply it to the United Arab Emirates tourism practice. This is because tourism, according to Islam, has clear purposes, despite the multiplicity of its concept, making it a standard on which contemporary tourism can be evaluated. Nowadays, tourism is of multiple concepts, with diversity in its fields as well as varying purposes, owing to the developments in the entire life spectrums, leading some countries to build their economy on tourism. Therefore, the research problem lies in clarifying the concept of contemporary tourism, highlighting its pros and cons, and identifying the principles and etiquettes guiding orthodox modern tourism, which are within the purposes of tourism set by the Prophetic Sunnah. The UAE was chosen for this study due to its status as one of the leading international tourism destinations. The subject in question was researched in four chapters apart from the introduction. The first chapter throws light on the concept of tourism, its origin and its development, while the second chapter highlights the different kinds of tourism as well as their purposes, principles, and etiquettes in the Prophetic Sunnah. The third chapter addresses tourism in the UAE regarding its origin and fields and its impact on the economy. In the fourth and final chapter, the researcher applied the Sharia purposes related to tourism to the UAE by analyzing its general laws and regulations on tourism in all its fields to determine whether these laws and regulations serve the purposes of Sharia in tourism. To actualize the objectives set by this study, the researcher employed inductive, descriptive, and analytical methods. The inductive method was adopted to explore the Prophetic sayings related to tourism and the opinions of Islamic scholars and hadith commentators regarding these sayings. The descriptive approach was used to describe the areas of tourism in the UAE in general and Abu Dhabi, Dubai and Sharjah in particular. The analytical method was employed to analyze the Prophetic Sayings related to the subject and deduce the tourism principles and etiquettes to govern the tourism practice in the state. The study concluded with some findings, the most important of which are: tourism has several literal and operational meanings in the Prophetic Sunnah. Its purposes in the Sunnah lie in the purification of the soul and preservation of Islamic fabrics. The principles and etiquettes of tourism in the Prophetic Sunnah governed the pre, during and post tourism activities. The UAE is ranked among the major tourism countries due to its interest in the environment and nature as well as the development of its tourism fields with the preservation of its religious identity of the state.